Chemodynamics of green pea galaxies - I. Outflows and turbulence driving the escape of ionizing photons and chemical enrichment - Hogarth, L. (2020)
We investigate the ionized gas kinematics, physical properties, and chemical abundances of Sloan Digital Sky Survey J142947, a Green Pea galaxy at redshift z ∼ 0.17 with strong, double-peak Ly α emission and indirect evidence of Lyman continuum (LyC) leakage. Using high-dispersion spectroscopy, we perform a multicomponent analysis of emission-line profiles. Our model consistently fits all lines as a narrow component with intrinsic velocity dispersion σ ∼ 40 km s-1, and two broader blue-shifted components with σ ∼ 90 and ∼250 km s-1. We find electron densities and temperatures, ionization conditions, and direct O/H and N/O abundances for each component. A highly ionized, metal-poor, young and compact starburst dominates narrow emission, showing evidence of hard radiation fields and elevated N/O. The blue-shifted broader components are consistent with highly turbulent, possibly clumpy ionized gas at the base of a strong photoionized outflow, which accounts for ≳50 per cent of the integrated emission-line fluxes. The outflow is dense and metal-enriched compared to the HII regions, with expansion velocities larger than those obtained from UV interstellar absorption lines under standard assumptions. Some of these metals may be able to escape, with outflows loading factors comparable to those found in high-z galaxies of similar SFR/Area. Our findings depict a two-stage starburst picture; hard radiation fields from young star clusters illuminate a turbulent and clumpy ISM that has been eroded by SNe feedback. Whilst UV data suggest an extended Ly α halo with high average HI column density, LyC photons could only escape from SDSS J142947 through low HI density channels or filaments in the ISM approaching density-bounded conditions, traced by outflowing gas.